พฤกษศาสตร์พื้นบ้านของชาวเขาเผ่ากะหร่างในจังหวัดประจวบคีรีขันธ์ - อรทัย เนียมสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The ethnobotanic study of Karang Hill Tribe in Pala-U village, Hua-Hin district, Prachuap Khiri Khan Province, was conducted from November 2001 to April 2004, by interviewing with Karang people about plant names in Karang language, and use of plant parts. Plant specimens were collected, photographed and identified. It was reported that one hundred and fifteen species were used by the Karangs. They were classified into 95 genera and 51 families except only one species which was unidentified. According to the utilization and properties, they can be divided into 5 groups, i.e. medicinal plants (51 species) food plants (42 species) plants for constructing and utensils (10 species) plants for other purposes (20 species) and poisonous plants (3 species). In this study, Sauropus thyrsiflorus Welzen, an endemic species of Thailand that has very limited distribution was found. In addition, thirteen medicinal plants that have never been recorded in any literatures were found. The traditional for plant use in Karang culture is closely related to Buddism. Therefore, the culture involving in plant utilization is expected to be diminished and possibly disappear later on due to the fact that more and more people in the tribe become Christians. In order to conserve this valuable tribal culture, the appropriate approaches should be discussed and performed by the authorized sectors. In the present study, descriptions of all families, genera and species are given together with the references of each name, ecology, distributions, utilization, local and karang names. Keys to genera, key to species and photographs of some interesting species are also included. All voucher specimens were kept at the Kasin Suvatabandhu Herbarium, Department of Botany, Faculty of Science, Chulalongkorn University.